2019
DOI: 10.1088/1755-1315/381/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of regional traffic dominance based on different indicators – taking Shandong Province as an example

Abstract: Taking Shandong Province as an example, select prefecture-level cities and county towns as research nodes, and use traffic network density (road network), proximity, and accessibility indicators to construct a comprehensive evaluation model of regional traffic dominance, using GIS network analysis and IDW. Spatial interpolation technique quantitatively analysed the spatial characteristics of the transportation network in Shandong Province. Through the spatial distribution characteristics of Shandong Province’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Currently, there have been more studies on the evaluation of traffic dominance, mainly focusing on the following aspects: firstly, the analysis of the spatial pattern of traffic dominance; and secondly, the analysis of the development relationship between traffic dominance and tourism, social economy, etc. Wang Yang, Tian Xiaoqin and other scholars, constructed a comprehensive evaluation model of traffic dominance and analyzed its spatial pattern [2][3][4][5] ; Liu Anle and other scholars, through the driving mechanism, found that the interaction intensity between traffic dominance and tourism development level in counties of central Yunnan city cluster is high [6] ; D Meng and other scholars, analyzed the relationship between traffic dominance and economic growth in Shandong province, and concluded that the spatial coupling is high [7] ; Yang Ren et al scholars analyzed the spatial synergy between the degree of transportation advantage and rural development in Chinese counties using models such as comprehensive evaluation, coupling coordination degree and spatial lag model [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there have been more studies on the evaluation of traffic dominance, mainly focusing on the following aspects: firstly, the analysis of the spatial pattern of traffic dominance; and secondly, the analysis of the development relationship between traffic dominance and tourism, social economy, etc. Wang Yang, Tian Xiaoqin and other scholars, constructed a comprehensive evaluation model of traffic dominance and analyzed its spatial pattern [2][3][4][5] ; Liu Anle and other scholars, through the driving mechanism, found that the interaction intensity between traffic dominance and tourism development level in counties of central Yunnan city cluster is high [6] ; D Meng and other scholars, analyzed the relationship between traffic dominance and economic growth in Shandong province, and concluded that the spatial coupling is high [7] ; Yang Ren et al scholars analyzed the spatial synergy between the degree of transportation advantage and rural development in Chinese counties using models such as comprehensive evaluation, coupling coordination degree and spatial lag model [8] .…”
Section: Introductionmentioning
confidence: 99%